Evaluation of the inhibitory effect of the cell-free fermentation filtrate of Bacillus atrophaeus YL84 on Fusarium oxysporum f. sp. vasinfectum and analysis of its metabolic products - Tang, Yuxin; Wang, Zhe; Feng, Hongzu; Wang, Lan (Frontiers in Microbiology, 2026)
To evaluate the biocontrol potential of the cell-free fermentation filtrate (CFFF) of Bacillus atrophaeus strain YL84 against Fusarium oxysporum f. sp. vasinfectum (FOV), this study systematically investigated the effects of the CFFF at various dilution ratios on FOV mycelial growth, conidial germination, cellular nucleic acid leakage, and malondialdehyde (MDA) content. Furthermore, the environmental stability of its antifungal activity was assessed. In addition, a dual-culture assay was conducted to evaluate the antagonistic activity of strain YL84 against FOV. The results of the dual-culture assay showed that strain YL84 significantly inhibited the growth of FOV, with an inhibition rate of 81.06%. Subsequently, the YL84 CFFF exerted significant inhibitory effects on FOV mycelial growth and conidial germination across different concentrations, achieving maximum inhibition rates of 75.68% and 77.56%, respectively. Notably, the treated mycelia exhibited a significant increase in cellular nucleic acid leakage and elevated levels of MDA, a product of lipid peroxidation, suggesting that the CFFF may disrupt the integrity of the pathogen’s cell membrane. Stability assays revealed that the CFFF possessed substantial tolerance to high temperatures, ultraviolet irradiation, and hypersaline environments, although it remained sensitive to strongly alkaline conditions. Greenhouse pot experiments further confirmed the efficacy of YL84 CFFF in controlling cotton Fusarium wilt, with a maximum control efficacy of 69.21%. Moreover, the treatment induced the upregulation of defense-related enzyme activities in the plants, suggesting that the CFFF may function through both direct antifungal action and the elicitation of host-induced resistance. Component identification via Ultra-Performance Liquid Chromatography–Ion Mobility–Quadrupole Time-of-Flight Mass Spectrometry (UPLC-IMS-Q-TOF-MS) suggested that the filtrate is rich in structurally diverse compounds that were putatively identified as potential antimicrobial substances, predominantly classified as terpenoids and their derivatives. In conclusion, this study provides a systematic evaluation and supporting evidence for the further development of B. atrophaeus YL84 as a biocontrol agent.